Patient and Technical Factors Associated with Difficult Arterial Access and Ultrasound Use in the Operating Room - Frank M. Yanko; Adovich Rivera; Eric C. Cheon; John D. Mitchell; Heather A. Ballard (MDPI AG, 2023)
Arterial catheterization enables continuous hemodynamic monitoring but has been shown to cause severe complications, especially when multiple attempts are required. The aim of this study was to explore what factors were associated with multiple attempts and ultrasound use in the operating room. We performed a retrospective analysis of patients who had arterial catheters inserted at a tertiary care children's hospital from January 2018 to March 2022, identifying clinical factors that were associated with both outcomes. A total of 3946 successful arterial catheter insertions were included. Multivariable analysis showed multiple attempts were associated with noncardiac surgery: pediatric (OR: 1.79, 95% CI: 1.30-2.51), neurologic (OR: 2.63, 95% CI: 1.89-3.57), orthopedic (OR: 3.23, 95% CI: 2.27-4.55), and non-radial artery placement (OR: 5.00, 95% CI: 3.33-7.14) (all p < 0.001). Multivariable analysis showed ultrasound use was associated with neonates (OR: 9.6, 95% CI: 4.1-22.5), infants (OR: 6.98, 95% CI: 4.67-10.42), toddlers (OR: 6.10, 95% CI: 3.8-9.8), and children (OR: 2.0, 95% CI: 1.7-2.5) compared to teenagers, with cardiac surgery being relative to other specialties-pediatric (OR: 0.48, 95% CI: 0.3-0.7), neurologic (OR: 0.27, 95% CI: 0.18-0.40), and orthopedic (OR: 0.38, 95% CI: 0.25-0.58) (all p < 0.001). In our exploratory analysis, increased odds of first-attempt arterial catheter insertion success were associated with cardiac surgery, palpation technique, and radial artery placement. Younger patient age category, ASA III and IV status, cardiac surgery, and anesthesiologist placement were associated with increased odds of ultrasound use.